Edible-Base Drinking Straw Coated of Carnauba Wax at Low Rate of Absorption in Banning Plastic Straw - Mohd Ghazali, Jamilah; Abdul Halim, Muhammad Haziq Azim; Norazman, Noranis Balqis; Azani, Nurul Aimi Adlina (Multidisciplinary Applied Research and Innovation, 2021)
Plastics today poses a major threat to marine life, animals and human health. After every single use, more than 50% of the manufactured plastics including straws, are disposed of. Fresh alternatives to disposable plastic straws are considered due to consumer demands for sustainability and recent changes in government policies and regulations, such as bans on single-use plastic products. The aim of this invention project was to develop an edible drinking straw as an alternative to plastic straws by using raw food-grade ingredients. The selected ingredients are food stabilizer, food humectant and food gelling agent. The paste preparation was the process where the specific amount of stabilizer, humectant and gelling agent were mixed using dough kneader. The paste being shaped through a straw shaping mold process before placing them into the drying oven. The straw formed was rigid since it comes at only 12% moisture content after the drying process with desired length of 15cm and small diameter of 0.6cm. Thereafter, the water-repellent coating comprises of carnauba wax which typically used in the candy industry was applied. Zebra Danio fish being fed with the straw and the pH meter of fish tank’s water showed the reading at 6.9 which is relevant to verify our straw toxicity. The study revealed that microbial growth is not active at low moisture content of dry food, however straw shelf life can only be predicted if the water activity of the straw being measured.